UJI AKTIVITAS ANTIBAKTERI EKSTRAK MAKROALGA Kappaphycus Striatum TERHADAP BAKTERI Pseudomonas Aerugimunosa: TESTING THE ANTIBACTERIAL ACTIVITY OF Kappaphycus Striatum MACROALGA EXTRACT AGAINST Pseudomonas Aerugimunosa BACTERIA - Al-Farabi, M. Naufal; Ratna, Isna Sri; Marshanda, Cindy; Putri, Velia Rima; Amelia, Restu; Putri, Elinda Triana (Journal of Animal Research and Applied Science, 2024)
Kappaphycus striatum seaweed is a seaweed better known as "sakul" which produces carrageenan. It has been widely cultivated because it has resistance to disease and is more adaptive than K. alvarezii. This research aims to find out how much the macroalgae Kappaphycus striatum can become an antibiotic from Pseudomonas sp bacteria. The method begins with maceration, taking the extract through a water bath, followed by making NA (Nutrient Agar) media for anti-bacterial testing The first 24 hours for a concentration of 10,000 the value of the inhibition zone is 2.17, then a concentration of 5,000 has a value of 2.10, a concentration of 1,000 has a value of 1.50, a concentration of 100 has a value of 1.60 and a concentration of 10 has a value of 1.50 2.07 for a concentration of 10,000, 1.63 for a concentration of 5,000, 1.60 for a concentration of 1,000, a value of 2.93 for a concentration of 100 and 1.13 for a concentration of 10. On the third day, the inhibition zone results were obtained with an average of 2.70 at a concentration of 10,000, 1.87 at a concentration of 5,000, 0.70 at a concentration of 10,000. concentration of 1,000, 1.37 at a concentration of 100 and 2.60 at a concentration of 10. Conclusions from the study This is Kappaphycus striatum, commonly known as "sakul," is a species of seaweed that is resistant to the bacteria Pseudomonas sp. The results showed that the inhibition zone varied at various concentrations over three days, with the highest inhibition zone at 2.70 mm for a concentration of 10,000 µg/ml on the third day, but with slightly fluctuating values